P358 THE ROLE OF ADHERENCE TO LIPID–LOWERING THERAPIES IN ACHIEVING LIPID TARGET: FINDINGS FROM REAL–WORLD ANALYSIS IN ITALY. (18th May 2022) - Degli Esposti, L; Borghi, C; Galvani, M; Giacomini, E; Manotti, P; Marra, A; Passaro, A; Perrone, V; Pieraccini, F; Sangiorgi, D; Navazio, A
Abstract: The objective of the present real–world analysis was to evaluate the impact of adherence to lipid–lowering drugs in reaching the lipid target in settings of clinical practice in Italy. The analysis was based on administrative and laboratory database of selected Healthcare Units in Italy covering approximately 10% of Italian population. Adult patients prescribed with statin and with at least a low–density lipoprotein (LDL) determination were included between 2012 and 2019. The index date was defined as the first prescription for statin within the inclusion period. Patients fell into 4 clusters collectively exhaustive and mutually exclusive based on their characteristics assessed during the year prior index date. Patients were considered as adherent if they had a proportion of days covered (PDC)≥80%. Among overall patients prescribed statin and with a LDL determination, 1% was with familial hypercholesterolemia, 28% with previous cardiovascular events, 21% with diabetes and 50% in primary prevention. Regardless their risk profile, the increasing of adherence was related to a higher achievement of LDL–target, with an increment of + 53.2% among familial hypercholesterolemia, +43.1% in diabetes and +30% in previous cardiovascular events and primary prevention clusters while progressing from low (PDC<40%) to high (PDC≥80%) levels of adherence. However, while in diabetes and primary prevention clusters 80% and 86% of adherent patients, respectively, had their cholesterol level under control, in the familial hypercholesterolemia and previous cardiovascular events clusters only 46% of adherent patients achieve the lipid target. The analysis showed adherence to be a key factor for cholesterol control. However, our findings underline a therapeutic need for patients that, although adherent, fail to achieve the lipid target, especially among patients with previous cardiovascular events (that have low level of LDL to achieve) and with familial hypercholesterolemia (that have high LDL basal level), suggesting therapeutic intensification should be applied.